Improved Ability to Deliver Negotiated Texts Through Articulation Learning Model - Zega, Imansudi; Zega, Aprianus; Harefa, Noveri Amal Jaya (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this study was to improve the ability of the class X MIPA-I SMA Negeri 2 Gunungsitoli even semester consisting of 36 people to convey negotiating texts through the Articulation learning model. To achieve this goal, the researchers carried out Classroom Action Research with the implementation procedures were (1) planning, (2) action, (3) observation, (4) reflection. The results of data analysis from the knowledge test in the first cycle reached an average value of 61.33 with the lowest score 52 and the highest 72. The knowledge value in the second cycle reached an average value of 84.33 with the lowest score 72 and the highest score 96. The results of analysis of student activity observation data in the first cycle of the first meeting with an average of 46.79% and the second meeting 52.35% (predicate "Less") and the second cycle of the first meeting with an average value of 65.38% and the second meeting 80, 55% (predicate “Good”). The results of the researcher's observations in the first cycle of the first meeting with an average value of 50% and the second meeting of 68.75%. While the results of the researchers' observations in the second cycle at the first meeting was 81.25% and the second meeting was 93.75%. Based on the explanation above, it can be concluded that: the use of the Articulation learning model can improve the ability to convey negotiating texts for students of class X MIPA-I SMA Negeri 2 Gunungsitoli. The recommended suggestions are the results of this study can be used as a guide in teaching the material to convey negotiating texts.